Berry density and size as factors related to the physicochemical characteristics of Muscat Hamburg table grapes (Vitis vinifera L.). (15th April 2015) - Rolle, Luca; Torchio, Fabrizio; Giacosa, Simone; Río Segade, Susana
Highlights: The impact of berry density and diameter as grape sorting methodologies was evaluated. Mechanical properties, phenolic composition and aromatic profile were determined. Berry density and diameter were related to mechanical traits and chemical composition. Densimetric sorting separated better berries according to their chemical composition. Abstract: The aim of this work was to determine the impact of using independently berry density and diameter as sorting methodologies on important physicochemical parameters affecting the grape quality, such as mechanical properties, phenolic composition and aromatic profile. Muscat Hamburg berries were classified according to the density by flotation in different salt solutions and to the diameter. The three most representative density (1081, 1088 and 1094 kg/m 3 ) and diameter (16–17, 18–19 and 20–21 mm) classes were selected. The results showed that there were relationships of both density and diameter with the mechanical properties and chemical composition of the berries. Densimetric sorting is a more promising methodology to separate grape berries with different quality attributes, particularly skin hardness, berry cohesiveness and resilience, total hydroxycinnamic acids, anthocyanins and rose oxide, than diameter sorting. This knowledge can be of great interest for the 'fresh-cut' industry in the production of 'ready-to-eat' fruits salad.